Automatic Design of Cable‐Tensioned Glass Shells - Laccone, Francesco; Malomo, Luigi; Froli, Maurizio; Cignoni, Paolo; Pietroni, Nico (Computer graphics forum, 2020)
We propose an optimization algorithm for the design of post‐tensioned architectural shell structures, composed of triangular glass panels, in which glass has a load‐bearing function. Due to its brittle nature, glass can fail when it is subject to tensile forces. Hence, we enrich the structure with a cable net, which is specifically designed to post‐tension the shell, relieving the underlying glass structure from tension. We automatically derive an optimized cable layout, together with the appropriate pre‐load of each cable. The method is driven by a physically based static analysis of the shell subject to its service load. We assess our approach by applying non‐linear finite element analysis to several real‐scale application scenarios. Such a method of cable tensioning produces glass shells that are optimized from the material usage viewpoint since they exploit the high compression strength of glass. As a result, they are lightweight and robust. Both aesthetic and static qualities are improved with respect to grid shell competitors. We propose an optimization algorithm for the design of post‐tensioned architectural shell structures, composed of triangular glass panels, in which glass has a load‐bearing function. Due to its brittle nature, glass can fail when it is subject to tensile forces. Hence, we enrich the structure with a cable net, which is specifically designed to post‐tension the shell, relieving the underlying glass structure from tension. We automatically derive an optimized cable layout, together with the appropriate pre‐load of each cable. The method is driven by a physically based static analysis of the shell subject to its service load. We assess our approach by applying non‐linear finite element analysis to several real‐scale application scenarios. Such a method of cable tensioning produces glass shells that are optimized from the material usage viewpoint since they exploit the high compression strength of glass. As a result, they are lightweight and robust. Both aesthetic and static qualities are improved with respect to grid shell competitors.